Distractions, Distortions and Dilemmas: The Externalities of Protecting Civilians in United Nations Peacekeeping. Issue 1 (2nd January 2022) - Day, Adam; Hunt, Charles T.
ABSTRACT: This article explores the unintended consequences associated with the protection of civilians (PoC) mandate in United Nations peacekeeping. Drawing primarily on two case studies – the Democratic Republic of the Congo (MONUSCO) and South Sudan (UNMISS) – we advance three lines of argument. First, the gravitational pull of PoC can distract missions from other, often interdependent, priorities. Second, the implementation of PoC can distort intended impacts. Third, these distractions and distortions can combine to produce dilemmas for mission architects, leadership and implementers. We conclude by identifying how these quandaries can ultimately make civilian protection, sustainable peace, and mission exits more elusive.